2018
DOI: 10.1186/s12872-018-0961-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac late events in German breast cancer patients: a validation study on the agreement between patient self-reports and information from physicians

Abstract: BackgroundSelf-administered health-status questionnaires are important tools in epidemiology. The objective of the presented validation study is to measure the agreement between breast cancer patients’ self-reports and their physicians’ information on late cardiac events, and to investigate determinants of agreement. To estimate possible misclassification is an important requirement for observational studies on cardiovascular endpoints.MethodsA retrospective, multi-center cohort study included 11,982 women dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…This is the first study to report that the agreement between self-reported and provider-reported comorbidities among older hospitalized patients with heart failure is generally poor. Though a direct comparison was not performed, the agreements of hypertension, diabetes mellitus, COPD, and coronary artery disease were numerically lower in patients with heart failure compared with the general elderly population, [1][2][3] patients with cancer, [10][11][12] and patients with chronic kidney disease, 13,14 which may be due to a variety of reasons. As the FRAGILE-HF study focused on older patients with heart failure, the patient population in this study included older patients, and age is a strong predictor of disagreement between patient reports and medical records regarding the presence or absence of comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is the first study to report that the agreement between self-reported and provider-reported comorbidities among older hospitalized patients with heart failure is generally poor. Though a direct comparison was not performed, the agreements of hypertension, diabetes mellitus, COPD, and coronary artery disease were numerically lower in patients with heart failure compared with the general elderly population, [1][2][3] patients with cancer, [10][11][12] and patients with chronic kidney disease, 13,14 which may be due to a variety of reasons. As the FRAGILE-HF study focused on older patients with heart failure, the patient population in this study included older patients, and age is a strong predictor of disagreement between patient reports and medical records regarding the presence or absence of comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…As the FRAGILE-HF study focused on older patients with heart failure, the patient population in this study included older patients, and age is a strong predictor of disagreement between patient reports and medical records regarding the presence or absence of comorbidities. 9,11,12,28 However, the cohorts evaluated in some previous studies were the same age or older than the patients included in this study. [1][2][3] Therefore, heart failure itself might have contributed to the poor agreement observed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, self-reported events may be prone to information bias due to restrictions in memory, a lack of fully understanding medical diagnoses, or selective reporting [ 40 ]. However, a validation study revealed moderate to fair agreement between self-reported events compared with medical records from general practitioners [ 41 ].…”
Section: Discussionmentioning
confidence: 99%